Health promotion of lesbian woman: nursing care - Josueida de Carvalho Sousa; Danielli Gavião Mallmann; Nelson Miguel Galindo Neto; Natália Oliveira de Freitas; Eliane Maria Ribeiro de Vasconcelos; Ednaldo Cavalcante de Araújo
The aim of this study was to analyze national and international scientific literature on nursing care for lesbian women. An integrative approach was adopted to review studies from MEDLINE, LILACS, BDENF and SCOPUS databases and SciELO and Cochrane libraries using the keywords: female homosexuality, nursing care, health promotion and women's health. Studies published between 1990 and 2013 in English, Portuguese or Spanish were considered for analysis. After analyzing data, four international studies were selected, being that three were from the United States and one was from Canada. This study revealed a scarcity of Brazilian and international studies and the importance of increasing scientific literature on this topic.